2019
DOI: 10.1515/rose-2019-2008
|View full text |Cite
|
Sign up to set email alerts
|

On the limiting spectral density of random matrices filled with stochastic processes

Abstract: We discuss the limiting spectral density of real symmetric random matrices. Other than in standard random matrix theory the upper diagonal entries are not assumed to be independent, but we will fill them with the entries of a stochastic process. Under assumptions on this process, which are satisfied, e.g., by stationary Markov chains on finite sets, by stationary Gibbs measures on finite state spaces, or by Gaussian Markov processes, we show that the limiting spectral distribution depends on the way the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The assumptions we made in Theorem 6.5 both on Z n and on the filling are but an example of the abstract assumptions given in [33]. These authors also show: Theorem 6.6.…”
Section: Decaying Correlationsmentioning
confidence: 73%
See 2 more Smart Citations
“…The assumptions we made in Theorem 6.5 both on Z n and on the filling are but an example of the abstract assumptions given in [33]. These authors also show: Theorem 6.6.…”
Section: Decaying Correlationsmentioning
confidence: 73%
“…The next step away from independence is to start with a sequence {Z n } n∈N of random variables and to distribute them in some prescribed way on the matrix entries X N (i, j). It turns out (see [33]) that the validness of the semicircle law depends on the way we fill the matrix with the random number Z n .…”
Section: Decaying Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we could fill it row-wise or sub-diagonal by sub-diagonal. For other sequences of random variables the way of filling the matrix may be crucial (see [21]).…”
Section: Remark 22mentioning
confidence: 99%
“…In [13,Theorem 5] it is shown that conditions (4) and (5) are well suited to apply the original ideas of Wigner [27,28] and Grenander [12] to prove the semicircle law via the method of moments (see also [2,3,18,21,22] and the monographs [1,4,23,25]). Matrix ensembles with correlated entries have already been considered in [5,7,8,10,11,14,19,24]. See [13] and the recent survey [16] for more information on these results.…”
Section: Observe That Pmentioning
confidence: 99%